Commercial and household food waste separation behaviour and the role of Local authority: A case study - Mamun Jamal; Aleksandra Szefler; Colman Kelly; Nicholas Bond (International Journal of Recycling of Organic Waste in Agriculture)
Purpose Source segregation of food waste is one of the major challenges that inhibit food waste recycling around the world. Therefore, the purpose of this study was to investigate the role of the local authority to implement regulations and encourage an increase in the source separation of food waste within both commercial premises and households, and identifying any gaps that exist in public awareness. Method This study was conducted by the Cork County Council in 568 commercial premises and 1362 houses in County Cork, Ireland. This study also included investigations of public and private civic amenity sites and waste collectors that collect kerb side waste located within the region. The intervieweeâs responses were documented and a database has been prepared and analyzed. Results Integrated strategy is crucial to roll out food waste bin within a community for successful implementation of source segregation of food waste. This strategy should involve a dedicated team from the local authority who continue to visit, monitor and co-ordinate the activities of local authorities, waste collectors, civic amenity sites and public to implement and enforce the food waste regulations. In addition to organizing appropriate infrastructure for recycling of food waste, continuous awareness raising through education, leaflets and local and national media is also crucial. Conclusion The role of local authorities should include facilitating the development of appropriate facilities such as composting, anaerobic digestion within communities and to encourage communities to take ownership of these facilities and reuse the resultant material within the local area.